Kemampuan Penalaran Matematis Mahasiswa Dalam Menyelesaikan Soal Tipe TIMSS Konten Data, Bilangan Dan Pengukuran - Nur Zahwa; Naqiyyah Nurrosyadah; Diva Maharani; Ratu Ilma Indra Putri; Zuli Nuraeni; Ruth Helen Simarmata (Universitas Pekalongan, 2023)
Reasoning in mathematics TIMSS is the lowest cognitive dimension achieved by students in answering questions. This is because students still have difficulty answering non-routine questions on TIMSS questions. Therefore, this research aims to determine students' mathematical reasoning abilities in solving TIMSS question on data content, geometry and measurement, and numbers. The method used is descriptive quantitative and qualitative methods through test and interviews. The results showed that students' mathematical reasoning ability was 66% for medium-level questions, 63% for high-level questions, and 29% for advanced-level questions. If it is averaged to 52.7%, it can be concluded that the mathematical reasoning of prospective mathematics teacher students in solving the TIMSS model development questions is still in the low category.Keywords: Data, Geometry & Measurement, Mathematical Reasoning, Numbers, TIMSSPenalaran dalam TIMSS matematika merupakan dimensi kognitif terendah yang dicapai siswa dalam menjawab soal. Hal ini dikarenakan siswa masih kesulitan dalam menjawab soal non rutin pada soal TIMSS. Oleh karena itu, penelitian ini bertujuan untuk mengetahui kemampuan penalaran matematis mahasiswa dalam menyelesaikan soal TIMSS konten data, geometri dan pengukuran, serta bilangan. Metode yang digunakan adalah metode deskriptif kuantitatif dan kualitatif melalui tes dan wawancara. Diperoleh hasil bahwa kemampuan penalaran matematis mahasiswa sebesar 66% untuk soal level sedang, 63% soal level tinggi, dan 29% soal level mahir. Jika di rata-ratakan menjadi 52,7% sehingga dapat disimpulkan bahwa penalaran matematis mahasiswa calon guru matematika dalam menyelesaikan soal pengembangan model TIMSS masih terkategori rendah.Kata Kunci: Bilangan, Data, Geometri dan Pengukuran, Penalaran Matematis, TIMSS